2022
DOI: 10.3390/nu14142941
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Status and Ca/Mg Ratios in a Series of Children and Adolescents with Chronic Diseases

Abstract: Magnesium (Mg) is an essential divalent cation involved in various enzymatic reactions that regulate vital biological functions. The main goal was to evaluate Mg status and its association with nutritional indicators in 78 children and adolescents with chronic diseases. We assessed anthropometric, biochemical, diet, body composition, and bone densitometry valuations. Serum Mg and Ca levels were determined using the standardized method and diet calcium (Ca) and Mg consumption by a prospective 72 h diet survey. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 181 publications
0
13
2
1
Order By: Relevance
“…Dietic factors are less likely to in uence serum magnesium levels in chronic conditions. [20] Serum magnesium levels were low in 5/6 (83.3%) patients with FSGS on biopsy, in contrast to 9/19 (47.4%) with MCD, but the difference was not statistically signi cant possibly due to a small sample size. Variability of magnesium wasting with the histopathology type has been described in a previous study.…”
Section: Discussionmentioning
confidence: 79%
“…Dietic factors are less likely to in uence serum magnesium levels in chronic conditions. [20] Serum magnesium levels were low in 5/6 (83.3%) patients with FSGS on biopsy, in contrast to 9/19 (47.4%) with MCD, but the difference was not statistically signi cant possibly due to a small sample size. Variability of magnesium wasting with the histopathology type has been described in a previous study.…”
Section: Discussionmentioning
confidence: 79%
“…In studies conducted on children with CP, magnesium levels were lower than those in the control group [23,31]. Hypomagnesemia was reported in 45% and hypermagnesemia in 12% of patients with a history of chronic disease [20]. In their study, Carman et al there was no signi cant difference between the magnesium levels of patients with CP and those of the control group [22].…”
Section: Discussionmentioning
confidence: 85%
“…Hypocalcemia has been the subject of studies in children who are critically ill [18,19]. Only Escobedo-Monge et al reported the occurrence of hypocalcemia in pediatric patients with a history of chronic disease, while Chidomere et al reported the occurrence of hypocalcemia in children with CP [20,21]. However, in a study by Carman et al, no signi cant differences were observed in calcium levels between patients with CP and a control group [22].…”
Section: Discussionmentioning
confidence: 99%
“…The design of this cross-sectional and comparative study (Figure 1) has been previously published [6,16,17]. This study was set up in the Nutrition Unit of the Pediatric Service at the University Clinical Hospital in Valladolid, Spain.…”
Section: Study Site Design and Participantsmentioning
confidence: 99%
“…Serum prealbumin ≤18 mg/dL, albumin ≤3.5 g/dL as visceral protein reserve, transferrin ≤200 mg/dL, lymphocytes <2000 cell/mm 3 , total cholesterol (TC) >200 (mildmoderate risk) and >225 mg/dL (high risk), and low-density-lipoprotein cholesterol (LDL-C) >115 (mild-moderate risk) and >135 mg/dL (high risk), were used as cutoffs to evaluate abnormal values. Total immunoglobulin (Ig) G levels, IgG1-4, IgA, IgM, and IgE, complement C3 and C4, CD3, CD4, CD8, CD16 + 56, CD19 T-lymphocytes and CD4/CD8 ratio, insulin-like growth factor −1 (IGF-1) and insulin-like growth factor-binding protein 3 (IGFBP3), folic acid, beta-carotene, Vit-B12, Vit-C, Vit-D, Vit-E, Ca, P, Fe, and Mg [17] were measured using standardized methods. Determination of serum Zn [16] and copper (Cu) [6] was carried out in the Department of Chemistry of the University of Valladolid.…”
Section: Laboratory Explorationmentioning
confidence: 99%